Taubat Sebagai Pedagogi Moral: Telaah Tematik Hadits Qudsi dalam Pendidikan Islam - Ronaa Fitri Butsainah; Nur Fatimatuzzahroh; Muhammad Akmansyah; Sultan Syahrir (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines the concept of repentance (taubah) as the foundation of moral pedagogy through a thematic interpretation approach to the Hadith Qudsi and classical and contemporary Islamic scholarly literature. The study employed a qualitative method based on literature review, examining the meaning, values, and educational implications of the teachings of repentance. The results of the study indicate that repentance is not merely understood as a spiritual act of seeking forgiveness, but as a holistic educational process. This process encompasses self-awareness (ma'rifah) of mistakes, deep regret (nadam), a strong determination not to repeat them ('azm), and concrete behavioral change ('amal). From an Islamic educational perspective, the values ​​of repentance play a crucial role in fostering moral responsibility, self-reflection, the habituation of good deeds, and a commitment to continuous self-improvement. The integration of repentance values ​​into learning can be realized through a character-based curriculum, reflective methods, strengthening worship practices, and moral development. Thus, repentance becomes an essential instrument in shaping a perfect human being who is faithful, has noble character, and possesses social awareness. Kata kunci: Taubat, Hadis Qudsi, Pedagogi Moral, Pendidikan Islam, dan karakter.